Anal and Rectal Diseases A Concise Manual - Ehrenpreis, Eli D.; avital, shmuel; Singer, Mark (Springer New York : Imprint: Springer, 2012)
Anal and Rectal Diseases: A Concise Manual provides a succinct reference on the subject for clinicians, including primary care physicians, gastroenterologists, general surgeons, physician's assistants and nurse practitioners. Presented in a consistent structural style that provides both a general summary of individual topics within the field along with additional details to assist those with some background knowledge in the subject area, this handy volume provides information related to the field of anorectal disease in a format that is easily accessible for rapid acquisition of knowledge. Each topic is outlined in a multidisciplinary fashion with the medical, surgical, and pathological aspects clearly detailed in each section. Each section clearly describes the condition with up-to-date management guidelines and precious clinical pearls. The volume features high quality illustrations in the form of elegant hand drawn figures, tables, photographs of physical findings, endoscopic finds and radiographs. The clinical photographs and x-rays will be of great value to gastroenterologists whose specialty is not coloproctology. Chapters on computerized tomographic colography (virtual colonoscopy) and others cover the newer technologies employed for diagnostic purposes in these diseases. Anal and Rectal Diseases: A Concise Manual provides clinicians with a tool for rapid consultation for direct patient care and management.